A systematic review of self-medication practice during the COVID-19 pandemic: implications for pharmacy practice in supporting public health measures - Zheng, Yu; Liu, Jiayu; Tang, Pou Kuan; Hu, Hao; Ung, Carolina Oi Lam (Frontiers in Public Health, 2023)
Introduction Since the COVID-19 pandemic, self-medication had become highly popular due to the risk of virus infection and overwhelming medical resources. Pharmacists are well-positioned to provide public health education and disease prevention. This study aims to provide an overview of the research about self-medication during COVID-19 and the role of pharmacists in ensuring the drug safety related to self-medication. Methods Databases (PubMed, Google Scholar, Scopus, EBSCO host, and Web of Science) were searched for published studies on the practice of self-medication in COVID-19 pandemic without restriction in population and location. Primary search terms were “self-medication,” “self-care,” “self-management,” “non-prescription drugs,” “2019nCoV,” and “COVID-19.” Studies conducted during the pandemic but not exclusively for COVID-19 disease were eligible for inclusion. Results The database search yielded a total of 4,752 papers. After appropriate screening, 62 articles met the inclusion criteria. Most of the studies were cross-sectional in nature. The review highlighted a very high prevalence of self-medication during COVID-19, ranging from 7.14 to 88.3%. The purpose of self-medication was mainly to treat and prevent COVID-19; fever, body aches, cough, headache, and sore throat were the most frequently mentioned indications. Categories of drugs commonly used in self-medication included antibiotics, herbs, vitamins, and analgesics, most of which came from pharmacies. Information about self-medication usually obtained from relatives and friends, social networks and health care professionals. Common reasons for self-medication included saving money and time, prior experience and mild illness; reasons associated with COVID-19 were mainly fear of contracting the virus and poor access to doctors. Gender, age, education, marital status, and concern about COVID-19 were the most usual associated factors. The role of pharmacists in self-medication included sources of information, advice on medication use, and management of adverse reactions. Conclusion During the COVID-19 pandemic, self-medication practices were widespread and varied across countries and populations. Self-medication has emerged as an important component of health care, but also as a huge global challenge. The engagement of healthcare administrators and policy makers are essential to regulate self-medication practices. The expertise and favorable conditions of pharmacists make them positioned as key roles in public health interventions for self-medication. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=395423, identifier CRD42023395423.